2023
DOI: 10.1111/ajae.12376
|View full text |Cite
|
Sign up to set email alerts
|

Incentive mechanisms to exploit intraseasonal price arbitrage opportunities for smallholder farmers: Experimental evidence from Malawi

Abstract: Seasonal commodity price fluctuations can potentially offer farmers arbitrage opportunities to increase their income. However, smallholder farmers in most of sub‐Saharan Africa often do not exploit these opportunities to the fullest extent possible. To inform this issue, we conducted a randomized controlled trial among 1739 smallholder farmers in Malawi to estimate the impact of two key post‐harvest constraints, lack of appropriate storage technology and commitment issues, on farmers' legume storage and sales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In Uganda, a similar study found increased use of hermetic bags occurred when there was a subsidy to assist with their initial purchase 93 . In Malawi, hermetic bags enabled smallholder farmers to store more legumes for longer periods of time 94 . These bags are as effective as, and often better than, pesticides in reducing storage losses due to insects 47,95,96 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In Uganda, a similar study found increased use of hermetic bags occurred when there was a subsidy to assist with their initial purchase 93 . In Malawi, hermetic bags enabled smallholder farmers to store more legumes for longer periods of time 94 . These bags are as effective as, and often better than, pesticides in reducing storage losses due to insects 47,95,96 .…”
Section: Discussionmentioning
confidence: 97%
“…47,95,96 They also improve food security and increase household income by providing safe storage for grain for household consumption and/or sale when food supplies are low and prices are high, with the availability of community storage for the bags further increasing the quantity of legumes stored and the duration of their storage. 94 In conclusion, hermetic bags can preserve quality of cereals, e.g. maize, paddy rice, and sorghum, and legumes, e.g.…”
Section: Mycotoxin Contaminationmentioning
confidence: 96%
See 1 more Smart Citation